miRNAs and their putative roles in the development and progression of Parkinson's disease - Wong, Garry; Nass, Richard (Frontiers in Genetics, 2013)
Small regulatory RNAs, such as miRNAs, are increasingly being recognized not only as regulators of developmental processes but contributors to pathological states. The number of miRNAs determined experimentally to be involved in Parkinson’s disease (PD) development and progression is small and includes regulators of pathologic proteins, neurotrophic factors, and xenobiotic metabolizing enzymes. PD gene-association studies have also indicated miRNAs in the pathology. In this review, we present known miRNAs and their validated targets that contribute to PD development and progression. We also incorporate data mining methods to link additional miRNAs with non-experimentally validated targets and propose additional roles of miRNAs in neurodegenerative processes. Furthermore we present the potential contribution of next-generation-sequencing approaches to elucidate mechanisms and etiology of PD through discovery of novel miRNAs and other noncoding RNA classes.